Denosumab Related Osteonecrosis of the Jaw with Spontaneous Necrosis of the Soft Palate: Report of a Life Threatening Case - Mohammed Qaisi; Jamie Hargett; Matthew Loeb; Jeffrey Brown; Ronald Caloss (Case Reports in Dentistry)
Bisphosphonates have been used for years in the treatment of patients with distant bony metastasis and in the prevention of osteoporosis. One of main side effects of these medications is the development of bisphosphonate related osteonecrosis of the jaw (BRONJ) in a small subset of patients. A new class of medications with a shorter half-life, known as receptor activator of nuclear factor kappa-B ligand (RANKL) inhibitors, was introduced with the hopes of avoiding this side effect. However, reports of osteonecrosis of the jaw after the use of RANKL inhibitors have also been documented. We report on a patient who developed a life threatening osteonecrosis of the jaw with sepsis shortly after switching from a bisphosphonate to a RANKL inhibitor for osteoporosis treatment. This patient developed several soft tissue defects including spontaneous necrosis of the soft palate. To our knowledge this is the first time this presentation has been described.